COVID‐19 and Independent Abortion Providers: Findings from a Rapid‐Response Survey. Issue 4 (9th December 2020) - Roberts, Sarah C.M.; Schroeder, Rosalyn; Joffe, Carole
Abstract : CONTEXT: The ways in which the COVID‐19 pandemic has affected abortion providers and abortion care, and the strategies clinics are adopting to navigate the pandemic, have not been well documented. METHODS: In April–May 2020, representatives from 103 independent abortion clinics (i.e., those not affiliated with Planned Parenthood) completed a survey that included close‐ended questions about how the pandemic, the public health response, and designations of abortion as a nonessential service had affected their clinic, as well as open‐ended questions about the pandemic's impact. Analyses were primarily descriptive but included an exploration of regional variation. RESULTS: All U.S. regions were represented in the sample. At 51% of clinics, clinicians or staff had been unable to work because of the pandemic or public health responses. Temporary closures were more common among clinics in the South (35%) and Midwest (21%) than in the Northeast and West (5% each). More than half of clinics had canceled or postponed nonabortion services (e.g., general gynecologic care); cancelation or postponement of abortion services was less common (25–38%, depending on type) and again especially prevalent in the South and Midwest. Respondents reported the pandemic had had numerous effects on their clinics, including disrupting their workforce, clinic flow and work practices; increasing expenses; and reducing revenues. State laws (including designations of abortion as nonessential) had exacerbated these difficulties. CONCLUSIONS: Although independent abortion clinics have faced considerable challenges from the pandemic, most continued to provide abortion care. Despite this resiliency, additional support may be needed to ensure sustainability of these clinics.